Molecular heterogeneity of clinically diverse cases of follicular thyroid carcinoma in next-generation sequencing: case report - Karunakaran, Poongkodi; Jayakumar, Deepak; Gurunathan, Raj Ashok (International Surgery Journal, 2024)
Thyroid cancer is the most common endocrine malignancy worldwide, with rising incidence. Follicular thyroid carcinoma (FTC) is the second most common thyroid cancer, accounting for 10% of thyroid cancer cases. FTC encompasses three different subtypes, with divergent clinical behavior. The encapsulated angioinvasive and minimally invasive subtypes have favorable outcomes. Whereas, the widely invasive subtype is associated with higher rates of hematogenous spread, refractoriness to radioactive iodine therapy and higher mortality rates. A better understanding of tumor biology can pave the way for targeted treatment strategies, optimizing the therapeutic outcome. To date, the molecular landscape of FTC is less well-characterized and poorly understood. Moreover, the clinical significance of the molecular characteristics of FTC remains elusive. Hence, we investigated genomic and transcriptomic profile of FTC using Next-Generation Sequencing in two patients with diverse clinical courses. This case report uncovered the molecular signatures, potentially unique to each patient, which may have clinical implications for risk stratification and personalized treatment strategies.